Spearhead Metal Ultramicroelectrodes Based on Carbon Nanoelectrodes as Local Voltammetric pH Sensors - Thomas Quast; Stefan Dieckhöfer; Wolfgang Schuhmann (Electrochemical Science Advances)
ABSTRACT We suggest a new method for preparing metal electrodes based on carbon nanoelectrodes (CNEs), which are suitable for application in shearforce scanning electrochemical microscopy (SECM). The as‐prepared CNEs were focused ion beam (FIB)‐processed, subsequently thermally recessed, and finally, Pt or Au were electrodeposited into the cavity of the recessed CNEs leading to insulator‐free metal electrodes with sizes of around 2 µm in diameter. For their application as local voltammetric pH sensors, the electrodes were calibrated in a concentration range of 11.6 M H+ to 9 M OH−. As a case study, we determined the local pH in situ using the developed Pt microelectrode positioned in close proximity to an Ag‐based gas diffusion electrode (GDE) which was operated for the oxygen reduction reaction (ORR). We could observe a shift of the Ptox reduction peak of ΔE = −700 mV, which is exceeding previous observations at Ag‐based GDEs by far. This novel type of electrode will pave the way to perform shearforce SECM with an even higher spatial resolution due to their spearhead shape.